The effects of artisanal small-scale gold mining on the environment: the case of ward 25 (Chisina 3) Gokwe south district - Mapfumo, Peter (Midlands State University, 2018)
The main aim of this research is to examine how artisanal small-scale gold mining undermines the environment which in the long run affect the livelihoods of the future generations in ward 25 (Chisina 3) in Gokwe south district. In Particular 10 operational mines 5 being Legal (registered) and 5 illegal (not registered) were under study. Qualitative research methodology was used in gathering relevant information from the respondents; this was done through the use of data gathering instruments which include interviews as well as questionnaires. 130 participants were reached through interviews as well as questionnaires. In terms of sampling method purposes sampling method was used, respondents were selected from the ward 25 residents, artisanal miners, mine associates as well as from village heads. Result from the study shows that there are several factors that triggered artisanal mining in the ward and these are ,droughts, massive unemployment, economic decline, abundance of gold deposits, the gold panning mindset amongst the local people, gold rush (riches) as well as easy accessibility of gold mines. In addition results from the study shows that artisanal small-scale gold mining result in environmental damages. The noted and observed environmental effects of artisanal gold mining include, land degradation, soil erosion and siltation, deforestation/vegetation, pollution (water, land, noise and air), destruction of soil organisms as well as the endangering of human beings.